The assisted reproductive technology (regulation) act, 2021: A step in the right direction - Vishan Dev Singh Jamwal; Arun Kumar Yadav (Wolters Kluwer Medknow Publications, 2023)
The Assisted Reproductive Technology (Regulation) Act, 2021, was passed on December 20, 2021 by an act of Parliament to regulate the functioning of assisted reproductive technology (ART) clinics and ART banks in the country. Since the dawn of in vitro fertilization (IVF), there has been a mushrooming of ART clinics in the country. There was need to supervise and regulate the functioning of these clinics and to safeguard the rights of women undergoing fertility treatment at these centers. The passing of this Act will go a long way in the better supervision, regulation, licensing, and smooth functioning of ART clinics and ART banks. The Act also brings into its ambit the controversial treatment of surrogacy and hence ensures protection of the rights of surrogate mothers. Moreover, strict implementation of the act will guarantee the success of the treatment within the legal and ethical framework.